Rhamnose polysaccharide-decorated outer membrane vesicles as a vaccine candidate targeting Group A Streptococcus from Streptococcus pyogenes and Streptococcus dysgalactiae subsp. equisimilis - Sowmya Ajay Castro; Sarah Thomson; Helen Alexandra Shaw; Azul Zorzoli; Benjamin H. Meyer; Mark Reglinski; Mark McNeil; Helge C. Dorfmueller (Vaccine: X)
Group A Streptococcus (Strep A) cause a wide range of human-exclusive infections, annually killing more than 500,000 people. Antibiotic resistance incidence of invasive Strep A tripled in the past decade and emphasises the need to develop a universal Strep A vaccine. In this study, we developed recombinant rhamnose polysaccharides (RhaPS), a validated universal Strep A vaccine candidate, presented on E. coli outer membrane vesicles (OMVs). We investigated OMV-RhaPS for their immunogenicity in the mouse and rabbit models. Through flow cytometry, ELISA, and immunofluorescence microscopy, we demonstrated that RhaPS-specific antibodies recognise Strep A strains via the Group A Carbohydrate (GAC) in S. pyogenes and the newly emerged S. dysgalactiae subsp. equisimilis. Elevated IL-17A levels from RhaPS-OMV-immunised splenocytes were detected when re-stimulated with the immunogen RhaPS-OMV. We report the efficacy and potency of recombinant produced RhaPS triggering antibodies that recognise Strep A bacteria and facilitate monocyte dependent opsonophagocytosis of several Strep A serotypes.